Comparative Study of Two Types of Distally Based Sural Neurocutaneous Flap for Reconstruction of Lower Leg, Ankle, and Heel - Dai, Jiezhi; Chai, Yimin; Wang, Chunyang; Wen, Gen; Liu, Shenghe; Zhang, Wei (Journal of Reconstructive Microsurgery, 2013)
Background Soft-tissue defects in the lower leg, ankle, and heel often require reconstruction with local or free flaps. We try to compare the clinical outcome and complications following transfer of a perforator pedicle–based sural neurocutaneous flap (P-NCF) or a fascia pedicle–based sural neurocutaneous flap (F-NCF).Methods Between March 2007 and December 2010, 92 patients (mean, 36.52 years) with a distal leg soft-tissue defect were included. Forty-eight patients treated with P-NCF were compared with 44 patients treated by F-NCF. The etiology, size, and operation time were noted. The clinical outcomes and the complications have been analyzed.Results Age, sex, and defect etiology, duration of surgery and, area of flaps did not reveal significant differences in term of clinical outcome. Minor flap necrosis (<10%) was observed in 20.5% of the F-NCF group and 6.25% of the P-NCF group. Patient satisfaction, aesthetic appearance, and functional outcome were comparable in both groups.Conclusion A high rate of complications was observed in the F-NCF group. Based on our finding, a perforator-based flap is more reliable than a fascia-based flap and the two types of flaps are both valuable choices for reconstructive surgery.
Keywords: distally based sural neurocutaneous flap; soft-tissue defects; reconstruction